Flow diverter treatment for proximal middle cerebral artery non-saccular aneurysms: multicenter efficacy and safety analysis - Yao, Hao; Zou, Chao; Zhu, Shijie; Wu, Yina; Sun, Jianfei; Lu, Zhiwen; Huang, Qinghai (Frontiers in Neurology, 2025)
ObjectiveProximal middle cerebral artery (MCA) non-saccular aneurysms present unique therapeutic challenges due to their morphology and proximity to critical branches. This study evaluates the safety, efficacy, and technical nuances of flow diverter (FD) devices in treating these lesions, with a focus on optimizing device selection and perioperative management.MethodsA retrospective multicenter analysis included 43 patients with M1/M2 segment non-saccular aneurysms treated with FD between 2020–2024. Perioperative antiplatelet regimens were individualized based on platelet function assays and genotype analysis for CYP2C19 polymorphisms. Procedural outcomes, complications, and angiographic results were assessed. Virtual stent simulation was utilized in 62.8% of cases for preoperative planning.ResultsFlow diverter (FD) implantation achieved 100% technical success. Perioperative complications occurred in 4.7% (2 transient deficits, 1 hemorrhage). Follow-up angiography (median 8.4 months; n = 38) demonstrated 92.1% complete occlusion (OKM-D), with 7.9% partial occlusion. In-stent stenosis occurred in 3 cases (7.9%), all asymptomatic. Clinical follow-up (median 25 months) revealed 97.7% favorable outcomes (mRS ≤ 2). Covered branches (M2, anterior temporal artery) exhibited stenosis in 23 cases and occlusion in 5, none clinically significant.ConclusionFlow diverter (FD) therapy for proximal MCA non-saccular aneurysms achieves high occlusion rates with low morbidity, particularly when combined with preoperative simulation and genotype-guided antiplatelet regimens. This study suggests that FD devices may serve as a potential alternative for traditional surgical treatment for this kind of aneurysms.